HUBUNGAN TINGKAT KEBUGARAN JASMANI DENGAN HASIL BELAJAR PJOK PADA PESERTA DIDIK KELAS VIII SMPN 1 SUNGAI TABUK KAB. BANJAR - Muhammad Renaldi; Lazuardy Akbar Fauzan; Edwin Wahyu Dirgantoro (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
The purpose of this study is to determine the relationship between the learning outcomes of Physical Education, Sports, and Health (PJOK) of grade VIII junior high school 1 Sungai Tabuk Banjar Regency and the level of physical fitness. This study combines a correlational strategy with a quantitative approach. Using a simple random selection method, a sample of 30 students was selected from a population of 90 students. The Indonesian Physical Fitness Test (TKJI) is used to measure the level of physical fitness of students aged 13 to 15 years, and the results of odd semester report cards are used to collect data on PJOK learning outcomes. Because the PJOK learning achievement data is not normally distributed, the normality test and the Spearman's rho nonparametric correlation test were used to analyze the data. The results showed that although the good group (83%) dominated PJOK's academic achievement, most of the students' physical fitness levels were in the moderate (43%) and poor (47%) categories. Physical fitness levels and PJOK learning outcomes had a strong and substantial positive relationship, according to the findings of the Spearman correlation test, which showed a coefficient value of 0.710 with a significance level of 0.000. According to these results, students are more likely to obtain the best PJOK learning outcomes if they are fitter.